Currículo e formação de professores de Ciências e Biologia : a cultura como eixo articulador dos projetos pedagógicos - Peixoto, Marco Aurélio Nicolato (2014)
This paper presents the thesis that the articulating shafts of knowledge should not be based on an affinity of contents (content axes) as occurs in current PPCs, but in cultural articulators axes. These axes are structured integrating disciplines considering cultural regional aspects, by internal representations that are consolidated in the students and the strong cultural background in which they live. As main goal it was intended to investigate and understand how it was processed the formation the training of Biology Professors in two federal institutions located in different cultural regions and subjected to the same training requirement of the Education e Culture Ministry (MEC). It was opted for a form of joint research that featured participant observation, interviews, data analysis and the technique of correspondence analysis (ANACOR), from a adapted procedure. It was used the program Statistical Package for Social Sciences (SPSS) allowing charts configuration that discharged in a perceptual map, providing a visual perception of the relationship between the menus of academic courses in question. The results showed that the Degree in Biological Sciences does not fit the different Brazilian realities. The need for supervision and formatting these courses ends up to mold them, or even format them in the light of a course project that ignores the peculiarities of our vast country, prevailing bureaucratic and administrative aspect over teaching aspects on the construction of PPCs. It is noticed that the content addressed is lacking of effective integration of specific and pedagogical disciplines. It is needed to break this fragmented culture, influenced by a positivist epistemology in which the parties do not join in the mind of the learner as one might expect. With this condition checked, it is proposed a never seen form of structuring PPCs .